Access and reimbursement pathways for digital health solutions and in vitro diagnostic devices: Current scenario and challenges - Mantovani, Andrea; Leopaldi, Claudia; Nighswander, Cassandra Maria; Di Bidino, Rossella (Frontiers in Medical Technology, 2023)
Objectives: Digital therapeutics (DTx) are innovative solutions that use meaningful data to provide evidence-based decisions for the prevention, treatment, and management of diseases. Particular attention is paid to software-based in vitro diagnostics (IVD). With this point of view, a connection between DTx and IVDs is observed. Methods: We investigated the current regulatory and reimbursement scenarios adopted for DTx and IVDs. The initial assumption was that countries apply different regulations for the access to the market and adopt different reimbursement systems for both DTx and IVDs. The analysis was limited to the US, European countries (Germany, France, and UK), and Australia due to maturity in digital health product adoption and regulatory processes, and recent regulations related to IVDs. The final aim was to provide a comparative overview and identify aspects that should be better addressed to support the adoption and commercialization of DTx and IVDs. Results: Many countries regulate DTx as medical devices or software integrated with a medical device, and some have more specific pathways. Australia has specific regulations classifying software used in IVD. Some EU countries are adopting similar processes to the Digital Health Applications (DiGA), which deems DTx eligible for reimbursement during the fast access pathway. France is working on a fast-track system to make DTx available to patients and reimbursable by the public system. The US retains coverage through private insurance, federal and state programs like Medicaid and Veterans Affairs, and out-of-pocket spending. The updated MDR and IVDR in the EU includes a classification system specifying how software integrated with medical devices, and IVDs specifically must be regulated. Conclusion: The outlook for DTx and IVDs is changing with them becoming more technologically advanced, and some countries are adapting device classifications depending on specific features. Our analysis showed the complexity of the issue demonstrating fragmentation of regulatory systems for DTx and IVDs. Differences emerged in terms of definitions, terminology, requested evidence, payment approaches and overall reimbursement landscape. The complexity is expected to have a direct impact on the commercialization of and access to DTx and IVDs. In this scenario, willingness to pay of stakeholders is a key theme.